Think two products ahead : - Mack, Benjamin (John Wiley & Sons, 2007)
This commonsense guide lets you develop your brand with the same techniques and technologies as the big players—but without all the cost. You’ll learn to master the same three-step plan the big advertisers use and discover the secret to brand continuity from product to product. This valuable resource will help you connect your products with your customers, no matter how small your brand.